2015
DOI: 10.1177/0004867415620024
|View full text |Cite
|
Sign up to set email alerts
|

Best strategies for reducing the suicide rate in Australia

Abstract: The evidence regarding the overall efficacy of the systems approach is important in identifying what strategies should be prioritized to achieve the biggest impact. The findings of the population preventable fraction calculations indicate that the systems approach could lead to significant reduction in suicide attempts and suicide deaths in Australia. Potential synergistic effects between strategies included in the approach could further increase the impact of implemented strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 20 publications
1
88
0
1
Order By: Relevance
“…14 In comparisons of the simulated effects of prevention strategies, the largest estimated impacts on declines in suicide were for GP training 17 and coordinated aftercare. 18 Simulated reductions in lethality of method by 20% for selected methods of suicidal behaviour (that is, assuming that interventions were available to reduce lethality of method) also suggested that the largest declines would be achieved with reductions in the lethality of hanging.…”
Section: Summary and Implications Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 In comparisons of the simulated effects of prevention strategies, the largest estimated impacts on declines in suicide were for GP training 17 and coordinated aftercare. 18 Simulated reductions in lethality of method by 20% for selected methods of suicidal behaviour (that is, assuming that interventions were available to reduce lethality of method) also suggested that the largest declines would be achieved with reductions in the lethality of hanging.…”
Section: Summary and Implications Of Findingsmentioning
confidence: 99%
“…A recent systematic review of peer-reviewed intervention studies was used to extract intervention effects for different health service-related suicide prevention initiatives 14 (Supplementary Table 5, available from: www.saxinstitute.org.au/tables-suicideprevention-tool). The strategies described in this review were selected because they are currently the subject of a large-scale community trial (www.lifespan.org.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15] It is drawing more and more attention day by day. 16 Means restriction is the restricting the availability of the lethal means of suicide.…”
Section: Means Restrictionsmentioning
confidence: 99%
“…8,10,11,14,[17][18][19]23 School can be ideal place for mental health literacy, suicide risk awareness, skill trainings those have significant effects on suicide prevention. 6 School based programs have proliferated as they have proven as cost effective and convenient way to reach the future generations.…”
Section: School Interventionsmentioning
confidence: 99%
See 1 more Smart Citation